Sprememba neplačanega reproduktivnega dela v plačano zaposlitev - Hrženjak, Majda (Družboslovne razprave, 2007)
In the article the author critically highlights the status of domestic work in contemporary societies, the asymmetrical sharing of domestic work between men and women and some measures for the reconciliation of work and family life which, according to the author, lead to the reproduction of women's inequality in the labour market. The articlećs main focus is the presentation of a pilot experiment of paid domestic work in households with small children. The pilot experiment found that the occasional use of paid domestic work has a positive influence on private life and relationships in the family; however, it barely influences the quantity of time women are spending on their careers. Beside that, the pilot experiment opened up the question of the precarious working conditions of contemporary informal domestic workers and their social invisibility. The author argues that the growing demand for paid domestic work in contemporary societies calls for the regulation and professionalisation of this area of informal work.
Keywords: Delo na domu; Home labor; Housework; Gospodinjsko delo; Zaposlovanje; Employment; Family; Družina; Kakovost življenja; standard of living; Quality of life; Slovenia; Slovenija; kvaliteta življenja